Hong Kong 2007-2017: a backlash in civil society. Issue 2 (3rd April 2017) - Chan, Elaine; Chan, Joseph
Abstract : Ten years ago, the development of civil society in the first decade of the Hong Kong Special Administrative Region (HKSAR) was analysed in terms of three discourses: civil society as a defender of its autonomy; civil society as the third sector; and civil society as a partner in governance. The conclusion then was that Hong Kong civil society had come of age; not only had its agenda been expanded, but there was also a diversification of values. Ten years on, this article updates the state of civil society, which can be described as both turbulent and vibrant. While Hong Kong society is deeply divided as a result of several mass mobilisations and the rise of localism, there has also been a mushrooming of counter forces in the form of social enterprises and informal groups aiming to help the underprivileged. Civil society has assumed a proactive and even aggressive role in protecting its values and autonomy (the first discourse), while its partnership in governance role has been seriously damaged (the third discourse). In its role as the third sector involving social capital (the second discourse), it has continued to flourish. However, there is a growing number of groups which spread ideas of exclusion and intolerance, and engage in practices like verbal abuse and physical violence, that are opposite to the values promoted by civil society. Accordingly, Hong Kong civil society is in urgent need of repair. If the un-civil values and behaviour are not checked, civil society will experience a downward spiral.